(x-1)²+3x=x+26
pfvr alguem me ajude
Soluções para a tarefa
Respondido por
1
É importante lembrar que
.
Então:
![(x-1)^2+3x=x+26 \\ (x-1)^2+2x=26 \\ x^2-2x+1+2x=26 \\ x^2+1=26 \\ x^2=25 \\ x=\pm5 (x-1)^2+3x=x+26 \\ (x-1)^2+2x=26 \\ x^2-2x+1+2x=26 \\ x^2+1=26 \\ x^2=25 \\ x=\pm5](https://tex.z-dn.net/?f=%28x-1%29%5E2%2B3x%3Dx%2B26+%5C%5C+%28x-1%29%5E2%2B2x%3D26+%5C%5C+x%5E2-2x%2B1%2B2x%3D26+%5C%5C+x%5E2%2B1%3D26+%5C%5C+x%5E2%3D25+%5C%5C+x%3D%5Cpm5)
Pois tanto 5² = 25 e (-5)² = 25
Então:
Pois tanto 5² = 25 e (-5)² = 25
Respondido por
0
(x-1).(x-1)= x²-2x+1+3x=x+26
x²-2x+3x-x+1-26=0
x²-25=0
x= +/- raiz quadrada de 25
x=+/- 5
x²-2x+3x-x+1-26=0
x²-25=0
x= +/- raiz quadrada de 25
x=+/- 5
Perguntas interessantes
Artes,
11 meses atrás
Ed. Física,
11 meses atrás
História,
11 meses atrás
Português,
1 ano atrás
Química,
1 ano atrás
Português,
1 ano atrás
Matemática,
1 ano atrás